Innovations and Obstacles (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
With increasing pressure to shift to sustainable means of agriculture and food demand, agricultural soils are facing strong human-induced stresses such as exceeding chemical inputs, improper application of pesticides, etc. Such activities have caused an imbalance in the soil microbiome, further disturbing microbe-mediated C, N and P cycles. Thus, it is time to modify soil properties and the microbiome with the aim of accelerating soil nutrient recovery and disease resistance. With increasing pressure on agriculture soils, microbiome-based strategies have exhibited tremendous potential. The emphasis has now shifted from the storage of potent individual strains to the preservation of beneficial microorganisms and to further establishing a healthy soil microbiome.